2013
DOI: 10.1186/1475-2859-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Why and how protein aggregation has to be studied in vivo

Abstract: The understanding of protein aggregation is a central issue in different fields of protein science, from the heterologous protein production in biotechnology to amyloid aggregation in several neurodegenerative and systemic diseases. To this goal, it became more and more evident the crucial relevance of studying protein aggregation in the complex cellular environment, since it allows to take into account the cellular components affecting protein aggregation, such as chaperones, proteases, and molecular crowding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Lack of eukaryotic post translational modifications and inclusion body formation are the main disadvantages. The improper conformation could make the expressed proteins undergo proteolytic degradation or aggregation (3). Intra- or inter-molecular disulfides bonds cannot be easily formed in the reducing cytoplasm of E. coli which facilitates aggregation of certain disulfide bond–rich proteins (4).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of eukaryotic post translational modifications and inclusion body formation are the main disadvantages. The improper conformation could make the expressed proteins undergo proteolytic degradation or aggregation (3). Intra- or inter-molecular disulfides bonds cannot be easily formed in the reducing cytoplasm of E. coli which facilitates aggregation of certain disulfide bond–rich proteins (4).…”
Section: Introductionmentioning
confidence: 99%
“…Because IBs contain highly ordered amyloid-like structures and their formation seems to share mechanistic features with amyloid self-assembly, they have been recently proposed as a model to study amyloid aggregation. 72,73 We have recently developed a methodology that allows a fast, simple, and inexpensive evaluation of the anti-aggregating activity of putative inhibitors, which is based on the in vivo staining with thioflavin S of IBs in intact E. coli cells that overexpress a given amyloidogenic protein in the presence and absence of the inhibitors, and monitoring of the corresponding changes in the fluorescence of thioflavin S. 74 The applicability of this method to the screening of both Aβ42 and tau aggregation inhibitors has been recently demonstrated. 74 Worthy of note, the Aβ42 anti-aggregating activities determined through this method for a number of known active and inactive inhibitors were very similar to those previously reported in in vitro assays using synthetic peptides, thereby validating this methodology.…”
Section: Inhibition Of Aβ42 and Tau Aggregation In Intactmentioning
confidence: 99%
“…Indeed, in living organisms proteins are prone to associate and interact with other cellular components, giving rise to complex interaction networks [23,24] that are absent in in vitro tests [25]. Thus, in vivo A aggregation is dependent on a number of factors that define its complex cellular environment [1,26,27], which cannot be captured in in vitro assays. Indeed, it has been suggested that A aggregation can proceed through different pathways in vitro and in vivo thereby leading to different A aggregates [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this light, bacteria have emerged as suitable models to monitor protein aggregation [27,28]. Protein aggregation also occurs during the production of heterologous proteins in prokaryotic systems, giving rise to insoluble protein aggregates, the so-called inclusion bodies (IBs), which limits the application of bacteria for recombinant protein production in the biotechnology industry [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation